Industri Pariwisata Ditinjau dari Etika Tanggung Jawab Hans Jonas - Ariani, Vitria (Humaniora, 2013)
Ecology is a system of balance between the elements of nature and man. Man as an animal that thinks has the concept of moral and responsibility toward himself, man with another man, and man with nature surroundings. Harmony or disharmony realization of ecological values is a concept of how to realize the appreciation of human values and the ideal of human interaction with the nature. Social norms, ethical values and social systems, the communication between people with other people and the world must take place in a positive, sustainable, and harmonious way. Technology makes man exploit nature for his own benefit. Advances in technology, on one hand, make human life easier. However, on the other hand, the progress has made natural destruction. Tourism is an activity that utilizes natural, social, and cultural resources that have broad impact on the development of tourism-related activities with the technology and activities in it. Tourism activities also have broad impact as as a multi-sectoral, multi-dimensional, and an integrated tourism industry to one and another. Ethics that puts the responsibility for Tourism Sustainability is the answers to minimize ecological damage to nature caused by the Tourism Industry.